1999
DOI: 10.1099/00207713-49-2-795
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus silvestris sp. nov., a new member of the genus Bacillus that contains lysine in its cell wall

Abstract: A Gram-positive, aerobic, rod-shaped, peritrichously flagellated, roundendospore-forming bacterium was isolated from a forest soil near Braunschweig, Lower Saxony, Germany, and designated strain HR3-23T (T = type strain). Morphologically, strain HR3-23T shows the characteristics of a member of the genus Bacillus. The spore position is terminal in a swollen sporangium. Comparative analysis of the 165 rDNA sequence shows strain HR3-23l to be most closely related to Caryophanon fenue (95.8% 165 rRNA similarity) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
56
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 37 publications
2
56
0
Order By: Relevance
“…Bacillus rRNA group 2 comprises six Bacillus species: Bacillus fusiformis, Bacillus globisporus, Bacillus insolitus, Bacillus pasteurii, Bacillus psychrophilus and Bacillus sphaericus, and also the nonBacillus species Sporosarcina ureae. An increasing number of species descriptions indicated the need to properly define the properties of the genus Bacillus (Farrow et al, 1994;Rheims et al, 1999;Stackebrandt & Swiderski, 2002;Kämpfer et al, 2006;Zhang et al, 2007) and according to Farrow et al (1994) the 'simplest and most phylogenetically consistent policy would be to exclude the group 2 bacilli from the genus Bacillus'. The same authors also suggested the transfer of B. globisporus, B. pasteurii and B.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Bacillus rRNA group 2 comprises six Bacillus species: Bacillus fusiformis, Bacillus globisporus, Bacillus insolitus, Bacillus pasteurii, Bacillus psychrophilus and Bacillus sphaericus, and also the nonBacillus species Sporosarcina ureae. An increasing number of species descriptions indicated the need to properly define the properties of the genus Bacillus (Farrow et al, 1994;Rheims et al, 1999;Stackebrandt & Swiderski, 2002;Kämpfer et al, 2006;Zhang et al, 2007) and according to Farrow et al (1994) the 'simplest and most phylogenetically consistent policy would be to exclude the group 2 bacilli from the genus Bacillus'. The same authors also suggested the transfer of B. globisporus, B. pasteurii and B.…”
mentioning
confidence: 99%
“…
Re-examination of the taxonomic position of Bacillus silvestris Rheims et al 1999 Following the transfer of three of the six species enclosed in the original definition of rRNA group 2 of Bacillus to the genus Sporosarcina and two to Lysinibacillus, other species of this group, some of which were added later, still await taxonomic revision. In a recent publication, a set of 'core' characteristics was proposed for species to be included in the genus Bacillus (Kä mpfer et al, 2006).
…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Cell morphology was investigated using slides covered with 2 % (w/v) agar (dissolved in water). Transmission electron microscope investigations were carried out as described previously (Rheims et al, 1999).…”
Section: Methodsmentioning
confidence: 99%